2011
DOI: 10.1016/j.bbamcr.2010.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a second messenger function of dUTP during Bax mediated apoptosis of yeast and mammalian cells

Abstract: The identification of novel anti-apoptotic sequences has lead to new insights into the mechanisms involved in regulating different forms of programmed cell death. For example, the anti-apoptotic function of free radical scavenging proteins supports the pro-apoptotic function of Reactive Oxygen Species (ROS). Using yeast as a model of eukaryotic mitochondrial apoptosis, we show that a cDNA corresponding to the mitochondrial variant of the human DUT gene (DUT-M) encoding the deoxyuridine triphosphatase (dUTPase)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…Uncovering unexpected cell survival sequences such as the Metalloprotease 15 (MMP15) suggests a novel role for extracellular matrix or alternative functions to well-known proteins (Abraham et al, 2005). The ability to increase cell survival by increasing the expression of the gene encoding dUTPase supports the emerging consensus that nucleotides such as dUTP serve as stress-induced pro-apoptotic second messengers (Williams et al, 2011; Wilson et al, 2012). On the other hand, the cytoprotective effects of the ceramide utilizing enzyme sphingomyelin synthase is consistent with the long standing role of ceramide as a stress-induced pro-apoptotic second messenger (Yang et al, 2006; Separovic et al, 2007, 2008).…”
Section: Regulation Of Programmed Cell Deathmentioning
confidence: 57%
“…Uncovering unexpected cell survival sequences such as the Metalloprotease 15 (MMP15) suggests a novel role for extracellular matrix or alternative functions to well-known proteins (Abraham et al, 2005). The ability to increase cell survival by increasing the expression of the gene encoding dUTPase supports the emerging consensus that nucleotides such as dUTP serve as stress-induced pro-apoptotic second messengers (Williams et al, 2011; Wilson et al, 2012). On the other hand, the cytoprotective effects of the ceramide utilizing enzyme sphingomyelin synthase is consistent with the long standing role of ceramide as a stress-induced pro-apoptotic second messenger (Yang et al, 2006; Separovic et al, 2007, 2008).…”
Section: Regulation Of Programmed Cell Deathmentioning
confidence: 57%
“…Previously, several studies indicated that the level of dUTPase protein decreases during apoptosis [36], [37], [38]. Moreover, the potentially significant role of dUTPase as an anti-apoptotic protein has been recently suggested [39]. This pathway of inducing apoptosis by calpain action may act in parallel to other described roles of calpain in apoptosis (e.g.…”
Section: Discussionmentioning
confidence: 92%
“…We speculate that if dUTPase activity could be impaired, under conditions that provoke dUTP accumulation and enhanced misincorporation into DNA, p53 exonuclease-proofreading activity might avoid mtDNA damage produced by the dUTP–DNA misincorporation pathway. Remarkably, the level of dUTP increases in response to certain stress signals [43]. Enhanced error-correction responses were observed following the IR stress-facilitated mitochondrial localization of p53, implying the increased DNA repair potential of p53 in stressed cells.…”
Section: Discussionmentioning
confidence: 99%